Adsorpsi Fosfat Pada Limbah Cair Laundry Skala Rumahan di Kabupaten Jember Menggunakan Karbon Aktif dan Zeolit Teraktivasi - Listifani, Dinissa Adinda; Pramitasari, Noven; Fildzah, Cantika Almas (Universitas Trunojoyo Madura, 2025)
Household-scale laundry wastewater contains phosphate, which poses significant environmental risks. This study aims to analyze the effectiveness of the adsorption process using activated carbon and activated zeolite in reducing phosphate concentrations from household laundry wastewater. The initial phosphate concentration in the wastewater was 5.19 mg/L. Adsorption was carried out using mass ratios of activated carbon and zeolite of 25:75, 50:50, and 75:25, as well as variations in zeolite activators using HCl and KOH. The research procedure included collecting laundry wastewater samples, drying and activating zeolite using 1 M HCl and 1 M KOH solutions, and mixing the adsorbents with wastewater in a batch system for 60 minutes under constant stirring. After the adsorption process, samples were filtered and analyzed for phosphate concentration using the spectrophotometric method. The results showed that the lowest phosphate concentration after adsorption was achieved with a mass ratio of activated carbon and zeolite activated by KOH at 25:75, which was 1.84 mg/L, with a phosphate removal efficiency of 64.5%. Statistical analysis using two-way ANOVA indicated that the mass ratio of activated carbon and zeolite significantly affected phosphate removal (p-value = 1.1 × 10⁻⁶), while the type of activator did not show a significant effect. This suggests that the appropriate mass ratio of activated carbon and zeolite can be an environmentally friendly and economical alternative for treating small-scale laundry wastewater.